Pendekatan Activity Based Learning Untuk Pembelajaran Bahasa Inggris di Sanggar Belajar Sido Mulyo - Pratiwi, Theodesia Lady; Zaki, Leil Badrah; Nugraha, Hendra; Ilmayana, Annisa Gina; Melyarisman, Tasya; Nugroho, Shabrina Shalma; Mamusung, Zico Kevin (STMIK Royal, 2025)
Abstract: English proficiency from an early age plays a significant role in shaping the competence of the younger generation to face global challenges. At Sanggar Belajar Tembesi Sidomulyo, English learning is not yet optimal because the teachers lack a for-mal educational background in the field, causing students to have difficulty mastering basic vocabulary, pronunciation, and understanding instructions. This research aims to address this problem by implementing an Activity Based Learning (ABL) approach, which emphasizes active student involvement through direct activities such as games, songs, visual simulations, and pronunciation exercises. This activity was carried out in four sessions on July 22, July 25, July 29, and August 4, 2025. Evaluation results indi-cate notable improvement. Among the five participating students, four students (80%) showed an average 20% increase in basic vocabulary mastery compared to pre-activity levels. Ninety percent demonstrated clearer pronunciation, and all students (100%) re-ported feeling enthusiastic and more motivated to learn. These findings confirm that the Activity Based Learning (ABL) approach is effective in enhancing participation and learning motivation while creating an enjoyable and meaningful learning experience. All students expressed interest in joining similar activities in the future. Keywords: activity-based learning; early english acquisition; vocabulary development; community service program; learner motivation; pronunciation improvement. Abstrak: Penguasaan Bahasa Inggris sejak usia dini memiliki peran penting dalam membentuk kompetensi generasi muda untuk menghadapi tantangan global di masa depan. Di Sanggar Belajar Tembesi Sidomulyo, pengajaran Bahasa Inggris belum optimal karena pengajar tidak memiliki latar belakang pendidikan formal di bidang tersebut, sehingga siswa mengalami kesulitan dalam penguasaan kosakata dasar, pelafalan, serta pemahaman instruksi. Penelitian ini bertujuan untuk mengatasi masalah tersebut dengan menerapkan pendekatan. Activity Based Learning (ABL), yang menekankan keterlibatan aktif siswa melalui aktivitas langsung seperti permainan, lagu, dan latihan pelafalan. Kegiatan ini dilaksanakan dalam empat sesi pada tanggal 22 Juli, 25 Juli, 29 Juli, dan 4 Agustus 2025. Hasil evaluasi menunjukkan peningkatan yang signifikan. Dari lima siswa peserta, empat siswa (80%) mengalami peningkatan penguasaan kosakata dasar rata-rata 20% dibandingkan sebelum kegiatan. Sebanyak 90% siswa menunjukkan per-baikan pelafalan, dan seluruh peserta (100%) menyatakan merasa senang serta lebih termotivasi mengikuti pembelajaran.Temuan ini membuktikan bahwa pendekatan Activity Based Learning (ABL) efektif dalam meningkatkan partisipasi dan motivasi belajar, sekaligus menciptakan pengalaman belajar yang menyenangkan dan bermakna. Seluruh siswa juga menyampaikan minat untuk mengikuti kegiatan serupa di masa mendatang. Kata kunci: activity-based learning; keterlibatan siswa; pembelajaran bahasa inggris; pembelajaran anak usia dini; sanggar belajar sidomulyo.